PENGOLAHAN LIMBAH CAIR RUMAH TANGGA DENGAN LUMPUR AKTIF YANG DIPACU ACLIMATED ARTIFICIAL SEWAGE - Pratiwi, Yuli (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2005)
This research is to know the effectivities of household processing biological with active mud pushed by acclimated artificial sewage, it is done by observing parameter DO (Disolved Oxygen), BOD (Biological Oxygen Demand), COD (Chemical Oxygen Demand), SS (Suspended Solid) and plankton as proponent data and then it is compared with quality standard included on SK Gubernur DIY No.281/KPTS/1998 about liquid waste. Household which is used for researching is from installation unit of waste water Sewon-Bantul. Waste is treatment with active mud pushed by acclimated artificial sewage concentration 0 % (control), 15 %, 30 %, 45 % with time of observation 0 hour, 2 hours, 4 hours, 6 hours, 24 hours. To know concentration of active mud to improve waste quality, it is used SPSS that is anava and Tukey test. The result of this research has shown that processing of household with active mud pushed by acclimated artificial sewage concentration 30 % is the most optimal and it can be improved: DO (63,64 %), BOD (74,06 %), COD (71,96 %), SS (65,57 %), where as the number of identified plankton is 24. The result of waste processing has been also suitable with quality standard of liquid waste included on SK Gubernur DIY No.281/KPTS/1998